Advances in automation and robotics research : proceedings of the 2nd Latin American Congress on Automation and Robotics, Cali, Colombia 2019 /: proceedings of the 2nd Latin American Congress on Automation and Robotics, Cali, Colombia 2019. (2020) - Unknown
No abstract available